Manipulativos Digitais no 1.º Ciclo : vamos aprender? - Gradíssimo, Maria Alice Sousa Dias, 1965- (2018)
This paper describes an intervention carried with a class of second graders. The study focused on the Mathematics and Art’s curricula outgoing from a digital manipulative (Magikplay) that was used to explore the game as a lever for the learning of concepts of geometry and art. The strategy used allowed the development of collaborative learning whereby students scaffold each other to solve the challenges presented by the game. The study revealed that the use of these tools promoted collaborative work, exchange of ideas and motivation for the creation of varied works